2006
DOI: 10.1111/j.1365-2966.2006.11078.x
|View full text |Cite
|
Sign up to set email alerts
|

Gas expulsion and the destruction of massive young clusters

Abstract: We examine the luminosity and dynamical mass estimates for young massive stellar clusters. For many young (<50 Myr) clusters, the luminosity and dynamical mass estimates differ by a significant amount. We explain this as being due to many young clusters being out of virial equilibrium (which is assumed in dynamical mass estimates) because the clusters are undergoing violent relaxation after expelling gas not used in star formation. We show that, if we assume that luminous mass estimates are correct (for a stan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
380
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(390 citation statements)
references
References 38 publications
8
380
2
Order By: Relevance
“…The earliest expansion is likely driven by the expulsion of leftover natal gas from very young clusters. Stars are left with a too large velocity dispersion for their new potential, and the cluster expands as it attempts to find a new equilibrium (Hills 1980;Goodwin & Bastian 2006). The amount of expansion depends on details of the gas expulsion (e.g., timescale, speed and fraction of gas that is lost, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The earliest expansion is likely driven by the expulsion of leftover natal gas from very young clusters. Stars are left with a too large velocity dispersion for their new potential, and the cluster expands as it attempts to find a new equilibrium (Hills 1980;Goodwin & Bastian 2006). The amount of expansion depends on details of the gas expulsion (e.g., timescale, speed and fraction of gas that is lost, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Goodwin 2009;Lamers, Baumgardt & Gieles 2010), infant mortality 1 (e.g. Lada & Lada 2003;Goodwin & Bastian 2006), star-formation rate in the Galaxy (e.g. Lamers & Gieles 2006;Bonatto & Bica 2011), among others.…”
Section: Introductionmentioning
confidence: 99%
“…For example it has been suggested that stars may form with initially sub-virial velocities that might allow the star clusters that form to remain in virial equilibrium even after gas dispersion (Offner et al, 2009;Smith et al, 2011). Alternatively if the star formation efficiency (the fraction of gas converted into stars) in these clusters was sufficiently high (>50%) then more gas would have been converted into stars during their formation and therefore the cluster may not have become unbound by the removal of the remaining gas potential (Goodwin & Bastian, 2006). Finally it has also been suggested that stars may naturally become spatially decou- showing the detailed structure revealed by these observations.…”
Section: The Role Of Kinematics In the Formation Of Star Clustersmentioning
confidence: 99%